Financial Resilience of Online-Based Micro Business During Covid-19 Pandemic - Ruth Samantha Hamzah; Efva Octavina Donata Gozali; Iwan Efriandy (AKUNTABILITAS, 2023)
The study investigates the effect of working capital management (WCM), firm size, and firm age on financial performance of online-based micro, small, and medium enterprises (MSMEs) in Palembang, Indonesia during Covid-19 outbreak. We used a quantitative-descriptive method which employed Ordinary Least Square (OLS) linear regression analysis. Questionnaire is distributed to food and beverages MSMEs and obtained 117 respondents as samples. The results proved that WCM has a significant and positive effect on financial performance, while firm size and firm age have no significant effect on financial performance. The result presents that managing working capital is crucial for MSMEs during Covid-19 pandemic, particularly the online-based MSMEs. The result is believed to deliver the implication for MSMEs owner-managers regarding decision making in order to improve their financial performance